Cyclical regulation of the insulin-like growth factor binding protein 3 gene in response to 1α,25-dihydroxyvitamin D(3) - Malinen, Marjo (Oxford University Press, 2011)
The nuclear receptor vitamin D receptor (VDR) is known to associate with two vitamin D response element (VDRE) containing chromatin regions of the insulin-like growth factor binding protein 3 (IGFBP3) gene. In non-malignant MCF-10A human mammary cells, we show that the natural VDR ligand 1α,25-dihydroxyvitamin D(3) (1α,25(OH)(2)D(3)) causes cyclical IGFBP3 mRNA accumulation with a periodicity of 60 min, while in the presence of the potent VDR agonist Gemini the mRNA is continuously accumulated. Accordingly, VDR also showed cyclical ligand-dependent association with the chromatin regions of both VDREs. Histone deacetylases (HDACs) play an important role both in VDR signalling and in transcriptional cycling. From the 11 HDAC gene family members, only HDAC4 and HDAC6 are up-regulated in a cyclical fashion in response to 1α,25(OH)(2)D(3), while even these two genes do not respond to Gemini. Interestingly, HDAC4 and HDAC6 proteins show cyclical VDR ligand-induced association with both VDRE regions of the IGFBP3 gene, which coincides with histone H4 deacetylation on these regions. Moreover, combined silencing of HDAC4 and HDAC6 abolishes the cycling of the IGFBP3 gene. We assume that due to more efficient VDR interaction, Gemini induces longer lasting chromatin activation and therefore no transcriptional cycling but monotonically increasing IGFBP3 mRNA. In conclusion, 1α,25(OH)(2)D(3) regulates IGFBP3 transcription through short-term cyclical association of VDR, HDAC4 and HDAC6 to both VDRE-containing chromatin regions.